Stay cool : a guy's guide to handling conflict - Hayhurst, Chris (New York : Rosen Central, 2000)
Examines various types of conflicts and suggests ways of solving them satisfactorily and peacefully.
Includes bibliographical references and index.
Keywords: Conflict management -- Juvenile literature; Teenage boys -- Psychology -- Juvenile literature; Teenage boys -- Conduct of life -- Juvenile literature; Young men -- Psychology -- Juvenile literature; Young men -- Conduct of life -- Juvenile literature; Conflict management